Bronchoalveolar lavage in ankylosing spondylitis. - Wendling, D (1990)
Bronchoalveolar lavage and bronchial biopsies were performed in 15 patients with ankylosing spondylitis (AS) and 17 control subjects. There was no difference in total cell count, number of lymphocytes, CD4+/CD8+ ratio, or beta 2 microglobulin concentrations in bronchoalveolar lavage fluid between these two groups. Bronchoalveolar lavage IgA concentrations were not increased, but bronchial IgA deposits were more common in AS. This study failed to show any subclinical alveolitis in AS.